1995
DOI: 10.2166/wst.1995.0532
|View full text |Cite
|
Sign up to set email alerts
|

Use of dissolved air flotation in potable water treatment in Finland

Abstract: The basic concepts of treating humic waters with dissolved air flotation are discussed emphasizing the important role of zeta potential in the forming of floc-air-bubble-agglomerates. Then practical experiences from Finnish drinking water treatment plants are presented. When surface water is used as a raw water, it is more or less humic. Thirty-six such plants have dissolved air flotation as a clarification process, the oldest one dating from 1965. They serve about one million people. All of them are working w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Później proces DAF był stosowany w oczyszczaniu ścieków i uzdatnianiu wody. Szczególne zalety tego procesu stwierdzono w oczyszczaniu wód powierzchniowych o niskiej mętności zanieczyszczonej organizmami fitoplanktonowymi lub substancjami humusowymi, zwłaszcza w okresach niskiej temperatury, kiedy obserwuje się niską skuteczność procesu sedymentacji [1][2][3]. Pierwsze aplikacje metody DAF do oczyszczania wód powierzchniowych miały miejsce w Skandynawii w latach 60. ubiegłego wieku.…”
Section: Wstępunclassified
See 1 more Smart Citation
“…Później proces DAF był stosowany w oczyszczaniu ścieków i uzdatnianiu wody. Szczególne zalety tego procesu stwierdzono w oczyszczaniu wód powierzchniowych o niskiej mętności zanieczyszczonej organizmami fitoplanktonowymi lub substancjami humusowymi, zwłaszcza w okresach niskiej temperatury, kiedy obserwuje się niską skuteczność procesu sedymentacji [1][2][3]. Pierwsze aplikacje metody DAF do oczyszczania wód powierzchniowych miały miejsce w Skandynawii w latach 60. ubiegłego wieku.…”
Section: Wstępunclassified
“…W celu sprawdzenia wykonalności proponowanych metod przeprowadzono badania laboratoryjne. Wodę do badań przygotowano z wody wodociągowej zanieczyszczonej ekstraktem kwasów humusowych w dawce 13,6 cm 3 /dm 3 Po przeprowadzeniu oczyszczania wody dokonano oceny jej jakości z wykorzystaniem spektrofotometru Hitachi U-2001 w celu oznaczania barwy wody i mętnościomierza Hach 2100N do oznaczania mętności wody.…”
Section: Badania Laboratoryjneunclassified
“…Japanese, in equipment and technology, had more extensive research and accessed a number of patents. Finlander used air flotation to clean water, from 1965 to 1992, 36 water treatment factories for drinking water were established, the total daily water purification capacity was 263,552m 3 and could supply for about one million people that was 20% of total population of Finland [4]. Swedish, as Finlander, had more than 100 large and small air flotation water treatment factories.…”
Section: History and Development Of Air Flotationmentioning
confidence: 99%
“…In China the use of air flotation technology started late, in the late of 1960s, dissolved air flotation devices were used in the salt making industry and oil wastewater treatment, due to technical problems, they were unrewarding [4]. In the design and test process of the wastewater treatment plant of Suzhou Cotton Textile Factory in 1975, the researchers found that the light weight particles in the printing and dyeing wastewater could be quickly gathered.…”
Section: History and Development Of Air Flotationmentioning
confidence: 99%
“…The technology was then adapted to treat water and wastewater through dissolved air flotation (e.g. Heinänen et al, 1995). Ultrafiltration membranes in turn have been mainly used for drinking water production (2 million m 3 /day worldwide according to Laîné et al, 2000).…”
Section: Introductionmentioning
confidence: 99%